Rainfall-induced landslides by deficit field matric suction in unsaturated soil slopes - Kim, Junghwan (2019)
Landslides are mainly triggered by decrease in the matric suction with deepening the wetting band by rainfall infiltrations. This paper reports rainfall-induced landslides in partially saturated soil slopes through a field study. A comprehensive analysis on Umyeonsan (Mt.) landslides in 2011 was highlighted. The incident involves the collapse of unsaturated soil slopes under extreme-rainfall event. Fundamental studies on the mechanism and the cause of landslides were carried out. A number of technical findings are of interest, including the failure mechanism of a depth of soil and effect of groundwater flow, the downward movement of wetting band and the increase of groundwater level. Based on this, an integrated analysis methodology for a rainfall-induced landslide is proposed in this paper that incorporates the field matric suction for obtaining hydraulic parameters of unsaturated soil. The field matric suction is shown to govern the rate of change in the water infiltration for the landslide analysis with respect to an antecedent rainfall. Special attention was given to a one-dimensional infiltration model to determine the wetting band depth in the absence of the field matric suction. The results indicate that landslide activities were primarily dependent on rainfall infiltration, soil properties, slope geometries, vegetation, and groundwater table positions. The proposed methodology has clearly demonstrated both shallow and deep-seated landslides and shows good agreement with the results of landslide investigations.